2011
DOI: 10.1128/aem.00703-11
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Nonsynergy Gamma Models and Interaction Models To Predict Growth of Emetic Bacillus cereus for Combinations of pH and Water Activity Values

Abstract: This research aims to test the absence (gamma hypothesis) or occurrence of synergy between two growth-limiting factors, i.e., pH and water activity (a w ), using a systematic approach for model selection. In this approach, preset criteria were used to evaluate the performance of models. Such a systematic approach is required to be confident in the correctness of the individual components of the combined (synergy) models. With Bacillus cereus F4810/72 as the test organism, estimated growth boundaries for the a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The gamma theory is, however, not always pertinent, and its applicability seems to depend on the organism, as well as on the combination of mild stress factors (27,39,40). Especially around the growth boundaries, the gamma model has shown poor agreement with experimental observations when no synergy factor was included (41). However, for L. monocytogenes, among other organisms, it was shown that further away from the growth boundaries, the gamma model without synergy generally performs well to describe the combined effect of water activity, pH, and temperature on growth (42).…”
Section: Discussionmentioning
confidence: 92%
“…The gamma theory is, however, not always pertinent, and its applicability seems to depend on the organism, as well as on the combination of mild stress factors (27,39,40). Especially around the growth boundaries, the gamma model has shown poor agreement with experimental observations when no synergy factor was included (41). However, for L. monocytogenes, among other organisms, it was shown that further away from the growth boundaries, the gamma model without synergy generally performs well to describe the combined effect of water activity, pH, and temperature on growth (42).…”
Section: Discussionmentioning
confidence: 92%